Identification of antimicrobial peptides from the Ambystoma mexicanum displaying antibacterial and antitumor activity - Nadjib Dastagir; Christina Liebsch; Jaqueline Kutz; Sabine Wronski; Andreas Pich; Doha Obed; Peter Maria Vogt; Vesna Bucan; Sarah Strauß (PLoS ONE, 2025)
Antibiotic resistance is a significant healthcare concern. Therefore, identifying target molecules that can serve as antibiotic substitutes is crucial. Among the promising candidates are antimicrobial peptides (AMPs). AMPs are defense mechanisms of the innate immune system which exist in almost all living organisms. Research on the AMPs of some amphibians has shown that, in addition to their antimicrobial effectiveness, AMPs also exhibit anti-inflammatory and anti-carcinogenic properties. In this study, we identify and characterize AMPs deriving from the skin mucus of the axolotl (Ambystoma mexicanum). Upon activity spectrum evaluation of the AMPs, we synthesized and ranked 22 AMPs according to antimicrobial efficacy by means of a prediction tool. To assess the AMPs’ potential as antibacterial and anticarcinogenic compounds, we performed a minimum inhibitory concentration (MIC) assay for efficacy against methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-sensitive Staphylococcus aureus (MSSA), and an apoptosis assay on T-47D mammary carcinoma cells. We identified four AMPs that showed significant inhibition of MRSA, of which three also demonstrated anticarcinogenic activity. Gene expression analysis was performed on AMP-stimulated carcinoma cells using a breast cancer-specific RT-PCR array. In cells stimulated with the AMPs, gene expression analysis showed upregulation of tumor suppressor genes and downregulation of oncogenes. Overall, our work demonstrates the antimicrobial and anticarcinogenic activity of axolotl-derived AMPs. The results of this work serve as a basis to further investigate the mode of action and potential use of axolotl AMPs as therapeutic anticancer or antibiotic agents.